Physiological, Biochemical, and Root Proteome Networks Revealed New Insights Into Salt Tolerance Mechanisms in Pongamia pinnata (L.) Pierre - Marriboina, Sureshbabu; Sekhar, Kalva Madhana; Subramanyam, Rajagopal; Reddy, Attipalli Ramachandra (Frontiers in Plant Science, 2022)
Cultivation of potential biofuel tree species such as Pongamia pinnata would rehabilitate saline marginal lands towards economic gains. We carried out physiological, biochemical and proteomic analysis to identify key regulatory which are associated with salt tolerance mechanisms at shoot and root level. Pongamia seedlings were grown at 300 and 500 mM NaCl (~3% NaCl; sea saline equivalent) concentrations for 15 and 30 days, gas exchange measurements including leaf net photosynthetic rate (Asat), stomatal conductance (gs) and transpiration rate (E) and varying chlorophyll a fluorescence kinetics were recorded. Further, whole root proteome was quantified using free labelled nanoLC-MS/MS technique to investigate crucial proteins involved in signalling pathways associated with salt tolerance. Pongamia showed no visible salt-induced morphological symptoms. However, Pongamia showed about 50% decline in gas exchange parameters including Asat, E and gs at 15 DAS (day after salt-treatment) and 30 DAS. The maximum potential quantum efficiency of Photosystem (PS) II (Fv/Fm) were maintained approximately 0.8 in salt-treated plants. Thermal component of PSII (DIo) was increased by 1.6-fold in salt treated plants. A total number of 1062 protein species were identified with 130 commonly abundant protein species. Our results also elucidate that there was a high abundance of protein species related to flavonoid biosynthesis, seed storage protein species and carbohydrate metabolism under salt stress. Overall, these analyses suggest that Pongamia exhibited sustained leaf morphology by lowering net photosynthetic rates and emitting most of its light energy as heat. Our root proteomic results clearly suggested that these protein species were most likely recruited from secondary and anaerobic metabolism, which could provide defence to root against Na+ toxicity under salt stress conditions.